Effects of Short-term Temperature Change in the Innocuous Range on Histaminergic and Non-histaminergic Acute Itch - Zoe Lewis; David N. George; Fiona Cowdell; Henning Holle (Medical Journals Sweden, 2018)
While temperatures in the noxious range are well-known to inhibit acute itch, the impact of temperature in the innocuous temperature range is less well understood. We investigated the effect of alternating short-term temperature changes in the innocuous range on histamine and cowhage-induced acute itch, taking into account individual differences in baseline skin temperature and sensory thresholds. Results indicate that cooling the skin to the cold threshold causes a temporary increase in the intensity of histamine-induced itch, in line with previous findings. Skin warming increased cowhage-induced itch intensity. Potential mechanisms of this interaction between thermosensation and pruritoception could involve cold-sensitive channels such as TRPM8, TREK-1 or TRPC5 in the case of histamine. The rapid modulation of cowhage induced itch - but not histamine-induced itch - by transient skin warming could be related to the lower temperature threshold of pruriceptive polymodal C-fibres (cowhage) as compared to the higher temperature threshold of the mechanoinsensitive C-fibres conveying histaminergic itch.